Nesting behavior of reintroduced Bornean Orangutan in Bukit Batikap Conservation Forest, Central Kalimantan, Indonesia - IKE NURJUITA NAYASILANA; SRI SUCI UTAMI ATMOKO; AHMAT SUYOKO; SUWARNO HADISUSANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Nayasilana IN, Atmoko SS, Suyoko A, Hadisusanto S. 2020. Nesting behavior of reintroduced Bornean Orangutan in Bukit Batikap Conservation Forest, Central Kalimantan, Indonesia. Biodiversitas 21: 2088-2096. Great apes such as orangutans build a nest to rest in every night. Orangutan’s nest making skills correlate with their adaptability in a new habitat. Here we analyzed the nest skill on the reintroduced orangutan. Skills process and thought training there is a back to remembers in forest school and pre-release islands in the rehabilitation center. The study aimed to observe the skill adaptation of reintroduced orangutans (semi-wild and ex-rehabilitate) for nest building and the characteristic of the tree chosen for their nests in a new habitat. The study was 16 individuals (8 semi-wild and 8 ex-rehabilitate) from February 2012 to November 2014 at the release site of Bukit Batikap Conservation Forest, Central Kalimantan. The method used in the study was instantaneous focal animal sampling, which follows the behavior of each orangutan from the morning nest to the night nest. Non-parametric statistics test (Kruskal-Wallis) was used to nesting behavior, Canonical Correspondence Analysis (CCA) is used to determine the relationship between nesting behavior and nesting tree species, and ArcMap GIS 10.3 to find out the distribution of nest trees in the research location. The result of the study revealed that reintroduced orangutan prefers to build a nest to rest at night rather than day nest. Semi-wild orangutans prefer tree species with dense canopy and branching, while ex-rehabilitation orangutans pay less attention to this. Mostly, reintroduced Bornean orangutan created new nests rather than reusing and/or repairing old nests. Species of Syzygium sp. Lithocarpus sp. and Xanthophyllum sp. are a preferred species of the nest tree, the nest position of 2 (nests are constructed on the main side-branch) and 3 (the crown of the tree) is dominance. Orangutan prefer height tree species between 26-30m for day nests, are selectively determined as part of the adaptation process. However, each individual will choose the nest type species of tree, positions, and height according to their characteristics of the nest tree.